Organization of SNAREs within the Golgi Stack - Malsam, Jörg; Söllner, Thomas (Cold Spring Harbor perspectives in biology, 2011)
Antero- and retrograde cargo transport through the Golgi requires a series of membrane fusion events. Fusion occurs at the cis- and trans-side and along the rims of the Golgi stack. Four functional SNARE complexes have been identified mediating lipid bilayer merger in the Golgi. Their function is tightly controlled by a series of reactions involving vesicle tethering and SM proteins. This network of protein interactions spatially and temporally determines the specificity of transport vesicle targeting and fusion within the Golgi.
Gesehen am 09.08.2022